Contrast-reversed binocular dot-pairs in random-dot stereograms for depth perception in central visual field: Probing the dynamics of feedforward-feedback processes in visual inference. (September 2021) - Zhaoping, Li
Abstract: In a random-dot stereogram (RDS), the spatial disparities between the interocularly corresponding black and white random dots determine the depths of object surfaces. If a black dot in one monocular image corresponds to a white dot in the other, disparity-tuned neurons in primary visual cortex (V1) respond as if their preferred disparities become non-preferred and vice versa, reversing the disparity sign reported to higher visual areas. Reversed depth is perceptible in the peripheral but not the central visual field. This study demonstrates that, in central vision, adding contrast-reversed dots to a noisy RDS (containing the normal contrast-matched dots) can augment or degrade depth perception. Augmentation occurs when the reversed depth signals are congruent with the normal depth signals to report the same disparity sign, and occurs regardless of the viewing duration. Degradation occurs when the reversed and normal depth signals are incongruent with each other and when the RDS is viewed briefly. These phenomena reflect the Feedforward-Feedback-Verify-and-reWeight (FFVW) process for visual inference in central vision, and are consistent with the central-peripheral dichotomy that central vision has a stronger top-down feedback from higher to lower brain areas to disambiguate noisy and ambiguous inputs from V1. When a RDS is viewed too briefly for feedback, augmentation and degradation work by adding the reversed depth signals from contrast-reversed dots to the feedforward, normal, depth signals. With a sufficiently long viewing duration, the feedback vetoes incongruent reversed depth signals and amends or completes the imperfect, but congruent, reversed depth signals by analysis-by-synthesis computation.